2007
DOI: 10.1063/1.2490563
|View full text |Cite
|
Sign up to set email alerts
|

Giant pop-ins and amorphization in germanium during indentation

Abstract: Thermal stability of metastable silicon phases produced by nanoindentationSudden excursions of unusually large magnitude ͑Ͼ1 m͒, "giant pop-ins," have been observed in the force-displacement curve for high load indentation of crystalline germanium ͑Ge͒. A range of techniques including Raman microspectroscopy, focused ion-beam cross sectioning, and transmission electron microscopy, are applied to study this phenomenon. Amorphous material is observed in residual indents following the giant pop-in. The giant pop-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
4
41
0
1
Order By: Relevance
“…These Raman spectra well agreed with those observed in previous works for a metastable polymorph of germanium, prepared either in diamond anvil cells60, or by a surface nanoindentation6162. In the literature, these spectra were attributed to a simple tetragonal lattice with 12 atoms per unit cell ( st12 , space group #96 – P 4 3 2 1 2) (also known as Ge-III)606162. Whereas, other papers reported different Raman spectra, e.g., a strong peak at near 200 cm −1 , and addressed them to another metastable polymorph with a body-centred cubic lattice with 8 atoms per unit cell ( bc8 , Ge-IV)63646566.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These Raman spectra well agreed with those observed in previous works for a metastable polymorph of germanium, prepared either in diamond anvil cells60, or by a surface nanoindentation6162. In the literature, these spectra were attributed to a simple tetragonal lattice with 12 atoms per unit cell ( st12 , space group #96 – P 4 3 2 1 2) (also known as Ge-III)606162. Whereas, other papers reported different Raman spectra, e.g., a strong peak at near 200 cm −1 , and addressed them to another metastable polymorph with a body-centred cubic lattice with 8 atoms per unit cell ( bc8 , Ge-IV)63646566.…”
Section: Resultssupporting
confidence: 90%
“…This pressure range covered the known phase transition from the original cubic-diamond-type lattice (Ge-I) to the metal phase with the β -Sn-type lattice (Ge-II) at about 10 GPa3031323334353637383940414243444546474849. As reported earlier, upon decompression, germanium can transform to one of its metastable polymorphs, instead of turning back to the cubic-diamond-type phase (Ge-I)555657585960616263646566. To verify the crystal lattice of the recovered from high pressure samples, we examined them by Raman and X-Ray diffraction studies (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Gogotsi et al using Raman spectroscopy found a phase transformation to occur very rarely and irreproducibly [12]. Bradby et al found that shear deformation by mechanical twinning and dislocation slip is the dominant deformation mechanism of Ge during nanoindentation [13,14]. Oliver et al found that the deformation mechanism of Ge during nanoindentation depends critically on the film thickness [15] and loading rate [16].…”
Section: Introductionmentioning
confidence: 96%
“…As in the case of Si, Ge undergoes a phase transformation towards a metallic-like b-Sn phase if exposed to a large enough pressure, typically in the order of $10 GPa. [19][20][21][22] It has been shown that the SSRMcontact can be described as a nano-indentation, whereby in a small volume below the probe, a high pressure is developed which can exceed the pressure range required for the phase transformation. 11 Although the affected volume is extremely small (few nm), its effect can be visualized by monitoring the impact of the force applied to the tip on the measured (spreading) resistance, leading to the so-called resistanceforce curve.…”
Section: A Resistance-force Curvesmentioning
confidence: 99%